A chromatin loop represses WUSCHEL expression in Arabidopsis. (10th May 2018) - Guo, Lin; Cao, Xiuwei; Liu, Yuhao; Li, Jun; Li, Yongpeng; Li, Dongming; Zhang, Ke; Gao, Caixia; Dong, Aiwu; Liu, Xigang
Summary: WUSCHEL ( WUS ) is critical for plant meristem maintenance and determinacy in Arabidopsis, and the regulation of its spatiotemporal expression patterns is complex. We previously found that AGAMOUS (AG), a key MADS‐domain transcription factor in floral organ identity and floral meristem determinacy, can directly suppress WUS expression through the recruitment of the Polycomb group (PcG) protein TERMINAL FLOWER 2 (TFL2, also known as LIKE HETEROCHROMATIN PROTEIN 1, LHP1) at the WUS locus; however, the mechanism by which WUS is repressed remains unclear. Here, using chromosome conformation capture (3C) and chromatin immunoprecipitation 3C, we found that two specific regions flanking the WUS gene body bound by AG and TFL2 form a chromatin loop that is directly promoted by AG during flower development in a manner independent of the physical distance and sequence content of the intervening region. Moreover, AG physically interacts with TFL2, and TFL2 binding to the chromatin loop is dependent on AG. Transgenic and CRISPR/Cas9‐edited lines showed that the WUS chromatin loop represses gene expression by blocking the recruitment of RNA polymerase II at the locus. The findings uncover the WUS chromatin loop as another regulatory mechanism controlling WUS expression, and also shed light on the factors required for chromatin conformation change and their recruitment. Significance Statement: Specific 3D chromatin change plays an important role in transcriptional regulation of target genes. Here, we demonstrated that two specific regions flanking WUSCHEL are sufficient and necessary for the formation of chromatin loop that is directly mediated by AGAMOUS and TERMINAL FLOWER2 during flower development. Thus, our findings uncovered a new layer regulation mechanism for WUSCHEL expression and shed light on the chromatin morphogenesis and subsequently spatial aspects of gene regulation.